Structural or functional abnormality of sphincter of Oddi: an important factor for the recurrence of choledocholithiasis after endoscopic treatment - Ye Yang; Zeying Zhao; Shuodong Wu; Dianbo Yao (Annals of Medicine)
A high recurrence rate is undesirable after treatment of common bile duct (CBD) stones. A major risk factor identified for recurrence is that invasive techniques, including surgical or endoscopic treatments, will impair the biliary tract system either by direct incision of the CBD or by cutting or dilating the ampulla of Vater. During endoscopic treatment, two main assisted methods for lithotomy, sphincterotomy and papillary balloon dilation, can result in different degrees of damage to the structure and function of the sphincter of Oddi (SO), contributing to slowing of biliary excretion, cholestasis, biliary bacterial infection, and promotion of bile duct stone recurrence. In this review, the relationship between endoscopic lithotomy and structural impairment or functional abnormality of the SO will be summarized, and their relationship with the recurrence of CBD stones will also be analyzed. Further improvement of these endoscopic methods or exploration of some novel methods, such as endoscopic endoclip papilloplasty, temporary insertion of a self-expandable metal stent, and combined application of peroral cholangioscopy, may aid in providing more appropriate treatment for patients with choledocholithiasis, repair or protect the function and structure of SO, reduce or prevent the recurrence of bile duct stones, and improve patient outcomes.